Changes in advanced protein structure during dense phase carbon dioxide induced gel formation in golden pompano surimi correlate with gel strength - Duan, Weiwen; Qiu, Hui; Htwe, Kyi Kyi; Wei, Shuai; Liu, Yang; Wang, Zefu; Sun, Qinxiu; Han, Zongyuan; Xia, Qiuyu; Liu, Shucheng (Frontiers in Sustainable Food Systems, 2023)
Changes in protein structure are closely related to gel strength. Dense phase carbon dioxide (DPCD) treatment is an excellent non-thermal food processing method that can be used to induce gel formation in surimi. The sensory, water holding capacity and gel strength of DPCD induced gels are superior to heat-induced gels. Fourier-transform infrared spectroscopy was used to investigate the role of DPCD in the quality of golden pompano surimi gels and changes in protein structure. The intermolecular forces of surimi gels were analyzed in terms of ionic and hydrogen bonds, disulfide covalent and non-disulfide covalent bonds, as well as hydrophobic interactions. Correlation analysis was used to investigate the relationship between the changes in advanced protein structure and gel strength during DPCD-induced gel formation in golden pompano surimi. The results showed that the α-helix and random coil levels of surimi gel were significantly decreased (p < 0.05), while the β-sheet and β-turn content was significantly increased (p < 0.05). The number of ionic and hydrogen bonds in gel proteins decreased significantly (p < 0.05), while the hydrophobic interactions, and disulfide and non-disulfide covalent bonds increased significantly (p < 0.05) after DPCD treatment. Correlation analysis showed that β-sheets, β-turns, hydrophobic interactions, and disulfide and non-disulfide covalent bonds were strongly positively correlated with gel strength, whereas α-helices, random coils, and ionic and hydrogen bonds were strongly negatively correlated with gel strength. Therefore, the α-helix and random coil structures of surimi gels were transformed into β-sheet and β-turn structures after DPCD treatment. Hydrophobic interactions, and disulfide and non-disulfide covalent bonds were the main intermolecular forces during the DPCD-induced gel formation of surimi. Ionic and hydrogen bonds were not the main intermolecular forces. The results provide fundamental data for elucidating the mechanism of DPCD-induced protein gel formation.